Analisis Sistem Pengendalian Internal Piutang pada KSP KPRI Bahagia Depag Jombang Tahun 2021 - Malikha, Putri Laili Nur; Ervina, Deasy (JFAS : Journal of Finance and Accounting Studies, 2024)
The purpose of this study was to analyze the internal control system of accounts receivable at the KSP KPRI Bahagia, Jombang Ministry of Religion in 2021. The method used in this study was a qualitative descriptive method. The data processed is the internal control system for accounts receivable at the KSP KPRI Bahagia Jombang in 2021. The data collection techniques used are observation, interviews and documentation. The results of this study indicate that the internal control system for the receivables of KPRI Bahagia Mora Jombang runs well and every year KPRI Bahagia MoRA Jombang has held a management meeting called RAT (Annual Member Meeting) in order to avoid fraud,, theft from parties. inside and outside the company.